Evaluasi Penggunaan Antibiotik Pada Pasien Pneumonia Rawat Inap Di Rsu Mitra Sejati - Nerly Juli Pranita Simanjuntak; Tasya Melisa Br Purba; Erida Novriani (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Pneumonia is a lower respiratory tract infection that remains a leading cause of death globally. Irrational use of antibiotics in its treatment worsens antibiotic resistance. This study aims to evaluate antibiotic use in hospitalized pneumonia patients at RSU Mitra Sejati using ATC/DDD and DU90% methods. This descriptive observational study used secondary data from adult inpatient medical records between January and December 2023. Results showed 37 patients, majority male (51.35%), mostly aged 26–35 and 56–65 years. A total of 273 antibiotic uses were recorded, dominated by third-generation cephalosporins, especially Cefixime 200 mg (31.14%). ATC/DDD analysis showed highest DDD/100 days for Cefixime 200 mg (21.04), Levofloxacin 500 mg (18.32), and Ceftriaxone 1 g (12.87). DU90% analysis identified six antibiotics comprising 91.04% of total use, indicating rational use according to national guidelines.